The Status of Anti-Piracy of The Optical Media Board: Basis for an Enhanced Standard Operating Procedure - Areglo, Maricel Fernandez (Future Science / FSH-PH Publications, 2024)
The rampant piracy issue in the Philippines has significant repercussions for both the entertainment industry and the government. To address this concern, the Optical Media Board (OMB) was established in 2003 as a government agency; responsible for enforcing intellectual property laws related to optical media. Despite the OMB’s efforts, piracy remains a persistent problem, particularly in the digital domain. The researcher conducted surveys among OMB personnel and licensed clients, utilizing a quantitative descriptive method and purposive sampling technique.The comprehensive evaluation of the OMB’s anti-piracy efforts revealed that the board was very effective in several key areas, including: intelligence/enforcement operations, information campaigns, digital piracy operations and quasi-judicial functions. Both OMB personnel and clients acknowledged the high effectiveness of these areas. However, there were perceptible differences in the perception of information campaigns among the respondents. The study recommends that the OMB intensify its efforts in this domain by disseminating information about piracy trends, emerging threats, and best practices to stakeholders. This collaborative approach aims to enhance the overall effectiveness of government-led anti-piracy initiatives. Furthermore, the challenges faced by the OMB are highlighted in the study, particularly the international nature of piracy operations, which is widely regarded as a formidable obstacle.